Domestic violence and the politics of privacy - Kelly, Kristin A. (Cornell University Press, 2003)
Privacy and domestic violence -- The family as a private entity -- Feminist re-visions of the public/private dichotomy -- The legal regulation of domestic violence -- The power of participation -- Reconstructing the boundaries of community concern.